Boiling point and specific heat of meat extract - Polachini, T. C. [UNESP] (2017)
Meat extract is a by-product obtained from the cooking broth of meat processing, which is used as a flavoring agent in cooking and in pharmaceutical products. Information on the processing technology of meat extract and its corresponding thermodynamic properties have been seldom reported, making difficult the design of heat transfer processes with accuracy. Thus, the present work aimed to evaluate the boiling-point elevation (BPE) and specific heat (cp) of meat extract in the range of concentrations and temperatures found during its processing. Boiling point temperature was determined experimentally as a function of pressure and soluble solid concentration of meat extract. Different correlations based on Dühring’s rule, Antoine equation, and the model proposed by Crapiste and Lozano were obtained to represent the boiling point temperature and/or BPE in some processing conditions, resulting in good fitting accuracy. The representation of the experimental values of cp was evaluated by four empirical equations. The best fitting was acquired using a quadratic model simultaneously dependent on concentration and temperature of the meat extract. The close agreement between the experimental and predicted values reinforces the applicability of the resulting models for designing evaporation systems.